Deliberation, Information Aggregation and Collective Decision Making - Otto H. Swank; Phongthorn Wrasai (Tinbergen Institute, 2002)
We study a model of collective decision making with endogenous information collection.Agents collect information about the consequences of a project, communicate, and then vote onthe project. We examine under what conditions communication may increase the probability thatgood decisions are made. Our most surprising result is that when there are no direct cost ofcommunication and communication can only help to identify the truth, more communication may reducethe probability that a correct decision is made. The reason for this result is that communicationmay aggravate the free-rider problem associated with collecting information.
Keywords: D78; D83; 330; Uncertainty; Deliberation; Learning; Collective decision making; Informationsverhalten; Informationsökonomik; Theorie; Politische Entscheidung